Pemikiran Pendidikan Islam Syekh Muhammad Naquib Al-Attas - Muslina Muslina; Rini Rahman (Program studi Keagamaan Islam, 2021)
This study aims to discuss and examine the thoughts of Sheikh Muhammad Naquib Al-Attas about Islamic education. The method used is a literature study, which uses library data as a source. The results of the study reveal that there are 5 (five) important points of Sheikh Muhammad Naquib Al-Attas' thoughts related to education, namely: First, the purpose of education, namely to instill goodness or justice in humans as human beings and personal self which focuses on the formation of individual personalities and expects the formation of an ideal society, Second, Educational Methods, The method he mostly uses is Tawhid, Metaphors and Stories, Third, Educational Curriculum, is divided into Fardhu 'ain and fardhu kifayah, Fourth Educators, according to Al-attas Educators must have personality and manners Fifth, students, according to Al-Attas, students are required to develop perfect etiquette in science